Tightrope act: Autophagy in stem cell renewal, differentiation, proliferation, and aging - Phadwal, K; Watson, A; Simon, A; Simon, A (2013)
Autophagy is a constitutive lysosomal catabolic pathway that degrades damaged organelles and protein aggregates. Stem cells are characterized by self-renewal, pluripotency, and quiescence; their long life span, limited capacity to dilute cellular waste and spent organelles due to quiescence, along with their requirement for remodeling in order to differentiate, all suggest that they require autophagy more than other cell types. Here, we review the current literature on the role of autophagy in embryonic and adult stem cells, including hematopoietic, mesenchymal, and neuronal stem cells, highlighting the diverse and contrasting roles autophagy plays in their biology. Furthermore, we review the few studies on stem cells, lysosomal activity, and autophagy. Novel techniques to detect autophagy in primary cells are required to study autophagy in different stem cell types. These will help to elucidate the importance of autophagy in stem cells during transplantation, a promising therapeutic approach for many diseases. © 2012 The Author(s).